Hindu Religious Ethics Values and Tolerance In Darmakaya's Gaguritan - Astawa, I Putu Yustika; Ni Made, Yunitha Asri Diantary (Jayapangus Press, 2023)
Gaguritan Darmakaya is one of the literary works that have a very high ethical value. As supported by the very wise, noble-hearted, calm and patient Pastor in guiding his disciples. Thus, with these characteristics, the Pandita was respected by his disciples. Likewise, the character I Darmakaya was a disciple who was always respectful to his teacher (the Priest), honest, friendly to others, skilled, and had good ethics. This study aimed (1). To find out the ethical values contained in Gaguritan Darmakaya, (2). To find out the ethical relationship of Hinduism with Gaguritan Darmakaya. This study used data collection methods, data processing, and analysis methods to study and examine more deeply. Data collection methods were used to explore data related to literature and explore data related to informants. Meanwhile, data processing methods were used to process data obtained through the libraries and interview results. Then, it was interpreted into sub-data to be presented in scientific papers. The data obtained through libraries and informants was processed descriptively by compiling systematically to get maximum results. After the data was composed, it was input into sub-data and interpreted to be presented as scientific papers. The theory used in this study was a theory of value related to ethics. The ethical value contained in Gaguritan Darmakaya was the ethics of self-control in the association of living together, which was contained in the advice from the Pandita to I Darmakaya so that after receiving knowledge to serve the Pandita selflessly.